MORPHOLOGICAL DIAGNOSIS - GOALS, OBJECTIVES, OPPORTUNITIES - Tursunov , Kh.Z.; Nishanov , D.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
The article provides general information about the goals, objectives and possibilities of morphological diagnostics in the practice of a pathologist. The procedure for preparing the drug in histological laboratories by conventional and immunohistochemical methods, their significance in the diagnosis of tumors is given in detail. The necessity and validity of improving the morphological diagnosis of diseases, especially oncological ones, using new technologies is indicated.